A interação entre as políticas fiscal, monetária e macroprudencial na economia brasileira - Oliveira, Pedro Henrique de (2019)
This work introduces fiscal policy in Divino and Kornelius (2015) general equilibrium stochastic general equilibrium model (DSGE), which contains financial frictions and a macroprudential policy, requiring reserve requirements. In view of this model, the role of the primary surplus and government spending as a means of propagating the shocks adopted in the model were analyzed. The results indicate that the presence of compulsory deposits increases the spread of monetary policy by reducing the level of credit. Public debt positively responds to real interest rate growth and tends to decline if not. Macro-prudential policy should not be a substitute for traditional monetary policy and should only stabilize the level of credit and leverage of the financial intermediation sector.